Defiant worldings from Manchester, England: Expulsed global solidarities and the international homeland of dignity. (1st June 2018) - Gräbner, Cornelia
This article explores contemporary material and affective traces of two instances of global solidarity in Manchester, England. The first is a letter sent to Abraham Lincoln by an assembly of Manchester citizens in December 1862, assuring Lincoln of their unwavering support for the struggle for the freedom of all despite the cotton famine's effect on those assembled. The second instance refers to the multi-faceted practices of solidarity with the Spanish Republic and the International Brigades. Drawing on Stephen D'Arcy's 'language of the unheard' and Ananya Roy's 'civic governmentality', and on commemorative traces in Manchester's topography, the article reflects on how 'defiant worldings' are commemorated, subordinated and/or marginalized but also how the spirit of egalitarian, anti-racist and anti-fascist defiance is remembered and kept alive.